PERANiGURUiDALAMiMELAKUKANiINTERNALISASIiNILAIiNILAI AGAMAiISLAMiUNTUKiMEMBENTUKiKARAKTERiPESERTAiDIDIK DIiMTSiAN - NUR 1IBULULAWANG - Afif Amrullah; Chalimatus Sa’dijah; Dzulfikar Rodafi (VICRATINA, 2020)
Character education is the priority in education today besides academic orientation. Through this character education, in the future it is hoped that the younger generation can get more power to fight the tide of globalization and can filter out all the negative aspects of the rapid development of globalization. Character education is a system of instilling character values carried out with the aim that students have the knowledge, awareness, and actions in implementing noble values in character building. In the system of inculcation of character values carried out in an Islamic educational institution using the Islamic values approach. As is the case in MTs An-Nur 1 Bululawang, In character education here has a variety of values - the same values as the values of Islamic religion, so it is very appropriate for us as a Muslim to develop character education with Islamic religious values. In this case, the value of the Islamic religion is sourced from the Qur'an and the Hadith in which it regulates all aspects of Muslim life. However, in this digital era, the current globalization that has entered it has already affected all aspects of the lives of Muslims so that Islamic religious values such as culture, lifestyle, social life fade. In each lesson, the teacher can associate general subjects with Islamic religious values, bearing in mind that in fact all knowledge comes from the Qur'an which guides Muslims, so that all subjects can be directly linked to Islamic religious values. Preliminary study research (2018) previously at Mts An Nur 1 Bululawang stated that in the school there was a phenomenon that students in the school were unable to obey the rules and did not carry out the orders that the school had set. In addition, based on the background above, there is still a lack of research that discusses the importance of internalizing or instilling aqidah moral in the school, so students cannot understand so often they do not obey the rules that have been set.